Ultracold atoms in optical lattices : simulating quantum many-body systems - Lewenstein, Maciej, 1955- (Oxford University Press, 2012)
This title explores the physics of atoms frozen to ultralow temperatures and trapped in periodic light structures. It introduces the reader to the spectacular progress achieved on the field of ultracold gases and describes present and future challenges in condensed matter physics, high energy physics, and quantum computation.